Asymmetric Decentralization and Policy Misalignment in Jakarta: A Systematic Review of Governance, Coordination, and Conflict Management - Sirod, Muhammad; Anang Puji Utama; Panji Suwarno; Arifuddin Uksan; Rachmat Setiawibawa (CV. ULIL ALBAB CORP, 2026)
This study systematically examines how asymmetric decentralization influences governance efficiency, intergovernmental coordination, and conflict management in Jakarta’s provincial administration. The research employs a Systematic Literature Review (SLR) method by analyzing 50 empirical studies selected through structured database searches, citation chaining, and relevance screening. The review focuses on key themes including administrative efficiency, policy-making dynamics, and mechanisms of conflict resolution within Jakarta’s unique decentralized governance structure. The findings indicate that decentralization enhances local government responsiveness and encourages policy innovation, allowing provincial authorities to address complex urban challenges more effectively. However, the implementation of asymmetric decentralization remains constrained by several structural issues, including institutional fragmentation, overlapping authority among governmental agencies, and inconsistent coordination across administrative levels. These challenges often reduce policy effectiveness and complicate governance processes. The study also highlights the growing potential of digital governance and participatory governance mechanisms to strengthen transparency, accountability, and policy coordination in metropolitan governance. Nevertheless, their implementation still faces limitations related to regulatory readiness, institutional capacity, and administrative integration. Overall, this study provides an integrated synthesis of Jakarta’s experience with asymmetric decentralization and offers context-sensitive policy insights for improving governance effectiveness in complex metropolitan regions while contributing to the broader theoretical discussion on asymmetric governance models.